A new 'turn-on' and reversible fluorescent sensor for Al3+ detection and live cell imaging. Issue 43 (22nd October 2019) - Wang, JianHua; Feng, LiHen; Chao, JianBin; Wang, Yu; Shuang, ShaoMin
Abstract : Herein, we report a new benzothiazole-based azomethine receptor L as a reversible fluorescent sensor for the selective detection of Al 3+ in buffered aqueous methanol (20 mM HEPES, pH = 6.0, 50% (v/v) CH3 OH). Abstract : Herein, we report a new benzothiazole-based azomethine receptor L as a reversible fluorescent sensor for the selective detection of Al 3+ in buffered aqueous methanol (20 mM HEPES, pH = 6.0, 50% (v/v) CH3 OH). The fluorescence enhancement response of L towards Al 3+ along with a large blue shift (Δ λ = ∼157 nm) may be attributed to the formation of the L–Al 3+ complex, which results in the inhibition of excited state intramolecular proton transfer (ESIPT) and CN isomerisation as well as the chelation enhanced fluorescence (CHEF). The results of Job's plot and mass spectroscopic analysis support the 1 : :1 stoichiometry of the complex between L and Al 3+ ions. The proposed complex structure was calculated by applying the DFT method. Furthermore, the applicability of the probe has been tested in BEL-7402 human hepatoma carcinoma cells under a fluorescence microscope, where turn-on, intense bluish green fluorescence was observed in the presence of Al 3+ ions.